Biological activity of dried infused sapodilla (Manilkara zapota) leaf tea formulated with different milk and sugar contents - PUTSON, Pathamaporn; WANIKORN, Bandhita; SAE-TAN, Sudathip; POOLSAWAT, Thitirat (Food Science and Technology, 2023)
Milk tea is a popular global beverage, but it also has high sugar and fat contents that can lead to chronic diseases. Sapodilla (Manilkara zapota) leaves contain various phenolic compounds with significant antioxidant and health benefits, but the biological impacts of interactions between sapodilla and other food ingredients in food systems have not been investigated. This study assessed ingredient interactions with the biological properties of functional sapodilla milk tea. Dried sapodilla leaves were infused with hot water at 1 g/120 mL and 1 g/68 mL and formulated with almond milk, soy milk, fat-free cow milk, and lactose-free cow milk. Each formulation was determined for color, total phenolic content, and total antioxidant activity using ABTS and FRAP assays. Two sweeteners, white sugar and smart-branded sugar, were added and tested for antioxidant capacity and sensory acceptability. The formulations were measured for estimated glycemic index (GI), antioxidant capacity, and sensory acceptability compared to commercial products. Results revealed a prototype with a lower estimated GI than commercial products (p<0.05) and high overall liking score of 7.6 (n=30). Functional ingredients from natural sources such as sapodilla leaves can be successfully incorporated into foods, providing novel functional product categories and new commercial opportunities.